Glasgow Coma Scale Scoring is Often Inaccurate. Issue 1 (9th December 2014) - Bledsoe, Bryan E.; Casey, Michael J.; Feldman, Jay; Johnson, Larry; Diel, Scott; Forred, Wes; Gorman, Codee
Abstract: Introduction: The Glasgow Coma Scale (GCS) is widely applied in the emergency setting; it is used to guide trauma triage and for the application of essential interventions such as endotracheal intubation. However, inter-rater reliability of GCS scoring has been shown to be low for inexperienced users, especially for the motor component. Concerns regarding the accuracy and validity of GCS scoring between various types of emergency care providers have been expressed. Hypothesis/Problem: The objective of this study was to determine the degree of accuracy of GCS scoring between various emergency care providers within a modern Emergency Medical Services (EMS) system. Methods: This was a prospective observational study of the accuracy of GCS scoring using a convenience sample of various types of emergency medical providers using standardized video vignettes. Ten video vignettes using adults were prepared and scored by two board-certified neurologists. Inter-rater reliability was excellent (Cohen's κ = 1). Subjects viewed the video and then scored each scenario. The scoring of subjects was compared to expert scoring of the two board-certified neurologists. Results: A total of 217 emergency providers watched 10 video vignettes and provided 2, 084 observations of GCS scoring. Overall total GCS scoring accuracy was 33.1% (95% CI, 30.2-36.0). The highest accuracy was observed on the verbal component of the GCS (69.2%; 95% CI, 67.8-70.4). The eye-opening component was the second most accurate (61.2%; 95% CI, 59.5-62.9). The least accurate component was the motor component (59.8%; 95% CI, 58.1-61.5). A small number of subjects (9.2%) assigned GCS scores that do not exist in the GCS scoring system. Conclusions: Glasgow Coma Scale scoring should not be considered accurate. A more simplified scoring system should be developed and validated. BE Bledsoe, MJ Casey, J Feldman, L Johnson, S Diel, W Forred, C Gorman .Glasgow Coma Scale scoring is often inaccurate .Prehosp Disaster Med .2015 ;30 (1 ):1 -8 .